Implementasi Metode ANP Terhadap Sistem Pendukung Keputusan Memilih Toko Daring Terbaik - Romindo Romindo; Jamaludin Jamaludin (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Today, online shops are in great demand by the people of Indonesia. Lazada, Shopee, Buka Lapak are a number of online stores that are quite popular in Indonesia. Students of the Ganesha Polytechnic are a small part of Indonesian people who are interested in buying at online stores. There is an increase and discussion among the Polytechnic students of Ganesha, in this case the difference is comparing which shops are the best. This debate is the purpose of this study. SuperDecisions is a decision support system which is an important requirement in the process of selecting the best online store. In the process of selecting a store, researchers also dare to use the Analytical Network Process (ANP) method as a problem modeling for complex results. The results of applying the ANP method to Shopee's decision process are the best online stores according to 3.80 Ganesha Polytechnic students, followed by Buka Lapak weighing 3.73 and Lazada with a weight of 2.47